2001
DOI: 10.1034/j.1600-0447.2001.104001012.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders among elderly people in primary care: the Linköping study

Abstract: Mental disorders and symptoms are common among the elderly in primary care. More effort should be made to increase the recognition rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 26 publications
4
42
1
1
Order By: Relevance
“…Many studies on psychiatric disorders in old age indicate that they are more prevalent in women than in men (Ó lafsdóttir et al, 2001;Hybels and Blazer, 2003;Ritchie et al, 2004). This is particularly true of depression and anxiety, which were over three times more frequent in women than in men in our study (Table 3).…”
Section: Gender Differencesmentioning
confidence: 42%
“…Many studies on psychiatric disorders in old age indicate that they are more prevalent in women than in men (Ó lafsdóttir et al, 2001;Hybels and Blazer, 2003;Ritchie et al, 2004). This is particularly true of depression and anxiety, which were over three times more frequent in women than in men in our study (Table 3).…”
Section: Gender Differencesmentioning
confidence: 42%
“…Taken together, these findings point to the need for the evaluation of suicide risks in elderly patients with minor depression. There is evidence that antidepressants are still underprescribed among nondemented very old persons with depression [30]. In our study, old elderly suicide victims with major or minor depression were less likely to receive treatment than their younger counterparts.…”
Section: Comparison With Previous Findingsmentioning
confidence: 56%
“…The Linkoping study in Sweden (Olafsdottir et al, 2001) found that among the 350 patients aged 70 yeas and above, the prevalence rate of psychiatric disorders was 33%, yet only 49% of them had been so diagnosed by the doctor. Furthermore, only 17-38% received specific treatments.…”
mentioning
confidence: 99%